O razširjeni solidarnosti na primerih prehranjevanja, povezovanja z rastlinami in izmenjevanja dobrin - Grabrijan, Enja (Etnolog. Nova vrsta (Ljubljana), 2025)
This article discusses the extent of solidarity networks. Following the ecofeminist perspective, which emphasizes the interconnectedness of the human and more-than-human, it presupposes the engagement in solidarity beyond species and in defiance of otherness. The author highlights some aspects of sustainable, regenerative, and reciprocal action through the examples of the exchange of goods, connecting with plants, and eating, thereby demonstrating how such efforts can be understood as extending solidarity.
Keywords: anthropology; antropologija; dobrine; ecofeminism; ekofeminizem; interconnectedness; more-than-human; reciprocity; recipročnost; regenerative; regenerativno; solidarity; solidarnost; več-kot-človeško